College Students’ Perceptions of their Core Competencies: An Institutional Analysis of Discipline and Gender - Sahbaz, Sumeyra; Culver, Steven M; Burge, Penny L (Advances in Social Sciences Research Journal, 2014)
In this study we examined the perceptions of 1,852 senior college students’ knowledge, skills, and abilities as freshmen and as seniors at a large research-intensive university in the southeastern United States. From a list of twelve core skills (e.g., critical thinking, writing, oral communication, leadership), we examined the underlying factors at both freshman and senior levels and explored differences by gender and by academic discipline. Using principal components factor analysis two distinct dimensions were extracted: (1) collaborative learning skills and (2) personal development. Using multiple multivariate analyses of variance (MANOVA), we found significant differences between male and female students in their perception of their skills and abilities both as entering and graduating college students in their oral communication skills, interpersonal skills and their ability to communicate with people different from themselves. Students from different academic disciplines (Engineering, Business, and Liberal Arts and Human Sciences) tended to perceive their proficiency level differently in terms of their interpersonal skills, leadership skills and ability to communicate with people different from themselves. Knowing areas where students differ in their skills and abilities can help faculty, administrators, and staff to re-examine curricula and to offer opportunities for all students to realize the personal, social, economic, and occupational benefits of a college education.